FACTOR AFFECTING INNOVATION MANAGEMENT THAT RESULT IN MARKETING SUCCESS AND COMPETITIVE ADVANTAGE FOR AGRICULTURAL OPERATORS THAT WILL LEAD TO THE ORGANIZATION PERFORMANCE - Pimonratnakan, Sudarat; Jadesadalug, Viroj (Journal of Humanities and Social Sciences Thonburi University, 2019)
The study of this literature aims to 1) Study the level of human capital development, entrepreneurial orientation, change management, business partner, innovation management, marketing success, competitive advantage, enterprises and the organization performance. 2) To examine the consistency of human capital development, entrepreneurial orientation, change management, business partner, innovation management, marketing success, and competitive advantage for agricultural operators. Impact of organizational performance on empirical data. 3) To study the human capital development, entrepreneurial orientation, change management, business partner, innovation management, marketing success, and the competitive advantage for agri-business operators and the organization performance. And the benefits of this literature review are guidelines for entrepreneurs to plan for the human capital development, entrepreneurial orientation, change management, business partner, innovation management, marketing success, and the competitive advantage for agri-business operators is that they provide good organizational performance from management and theoretical use, as well as further research approaches that are used more effectively. This will contribute positively to the organization's operations.